2007
DOI: 10.1021/jp072022e
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Blocking-Controlled Freezing of Water in Cagelike Pores of KIT-5

Abstract: To examine the mechanism of the thermal hysteresis between freezing and melting for water confined in a network of the ink-bottle pores of ordered silica, we measured the freezing and melting behavior of pore water in seven kinds of KIT-5 samples with various neck and cavity sizes by means of differential scanning calorimetry and X-ray diffractometry. The melting temperature of pore ice depended on the cavity size, whereas the freezing behavior of pore water depended on the neck size. When the neck size is sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 56 publications
7
68
0
Order By: Relevance
“…SBA-16 exhibits cage-like pores in the size range from 6 to 11 nm diameters that are interconnected by channels whose dimensions depend on the hydrothermal treatment temperature during synthesis (Kittaka et al, 2011). The mesoporous KIT-5 silica has spherical cavities (10-20 nm diameters) arranged in a face-centered cubic array and connected through narrow necks (Morishige et al, 2007). Zeolites are microporous crystalline aluminosilicates with pore diameters (D p ) between 0.3 and 1.2 nm.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SBA-16 exhibits cage-like pores in the size range from 6 to 11 nm diameters that are interconnected by channels whose dimensions depend on the hydrothermal treatment temperature during synthesis (Kittaka et al, 2011). The mesoporous KIT-5 silica has spherical cavities (10-20 nm diameters) arranged in a face-centered cubic array and connected through narrow necks (Morishige et al, 2007). Zeolites are microporous crystalline aluminosilicates with pore diameters (D p ) between 0.3 and 1.2 nm.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that microcrystals did not grow along the pore length but that many nuclei formed in each cylindrical pore. Freezing temperatures of KIT (Morishige et al, 2007) and SBA-16 samples (Kittaka et al, 2011) that lie between the solid grey and the dotted black lines in Fig. 3 are indicative of heterogeneous freezing within the cage-like pores initiated by ice that propagates through channels connecting the pores.…”
Section: Marcolli: Deposition Nucleation 2075mentioning
confidence: 98%
See 3 more Smart Citations